The influence of carbon-containing greenhouse gases on the dynamics of radial increment of Pinus cembra and Picea abies in the conditions of the Gorgany Nature Reserve - O. I. Moroz; O. N. Kuz; M. V. Ruda (Regulatory Mechanisms in Biosystems, 2020)
Based on the tree-ring chronology, we studied the radial increment of Swiss stone pine (Pinus cembra L.) and common spruce, or Norway spruce (Picea abies L.) as indicators of dendrochronological studies and, based on tree-ring chronology, reconstructed the annual changes of stem biomass and the amount of carbon accumulated in it by P. cembra and P. abies in the Gorgany Nature Reserve. Swiss stone pine stands are of great zoological importance as biotopes of nutcracker (Nucifraga caryocatactes L.), crossbill (Loxia curvirostra L.), capercaillie (Tetrao urogallus L.) and other representatives of rare boreal fauna. Samples were taken from trees of the Playa forest district of the Brusturyan Forest Hunting Range State Enterprise of the Transcarpathian Regional Forestry Administration (P. cembra and P. abies) from trees that did not have visual signs of damage in the Gorgany Nature Reserve. By cross-dating the radial increments of two radii for each tree, individual chronological series were drawn up. Carbon sequestration in P. cembra and P. abies stem wood was evaluated on the basis of dendrochronological analysis of radial increment. The accuracy of cross-dating of dendrochronological series of individual trees, individual chronological series, and representativeness of the generalized series were verified by conventional methods. It was found that the average annual radial increment of the trees under study is 11.48 mm in P. cembra and 14.39 in P. abies, and varies in the range of 1.86–5.49 mm. The data obtained indicate an increase in the ability of P. cembra and P. abies to accumulate carbon with increasing age. The study of carbon sequestration in the stem wood of P. cembra and P. abies, based on dendrochronological analysis, made it possible to reconstruct the annual variation in stem biomass increment and accumulated carbon. The analysis of interdependence of the radial increment of P. cembra and P. abies in the Gorgany Nature Reserve and the value of carbon-containing greenhouse gases in the atmosphere, carried out by the augmented data sample, made it possible to specify the periods most significant for the formation of annual rings. The reaction in radial increment is most pronounced from June to September, with the annual values of carbon-containing greenhouse gases being maximally reflected in radial increment for the period from October to April.